TRENDS OF SEXUAL ASSAULT CASES - walia, Didar Singh; Kukreja, Sumit; Aggarwal, Akashdeep; Chahal, Preetinder Singh; Singh, Satinder Pal (Journal of Forensic Medicine and Toxicology, 2021)
The World Health Organization defines sexual violence as “any sexual act, attempt to obtain a sexual act, or other act directed against a person’s sexuality using coercion, by any person regardless of their relationship to the victim, in any setting”. This includes rape, indecent assault, sexual harassment and threats. This study was conducted in the casualty unit over a period of two years (September 2018 to September 2020), total 35 cases of communities remains unknown. Most commonly victims are female rarely will a heterosexual male report that he has been a victim of this type of assault. General definition of sexual assault includes all those victims involving unwanted sexual contact occurring between the victim and assailant. Sexual violence refers to sexual activity where consent is not obtained or freely given.2 Sex crimes are complex and multidimensional. Children and adolescent oriented sexual assaults are increasing.3
Keywords: sexuality using coercion; study